Online Customer Experience Leads to Loyalty via Customer Engagement: Moderating Role of Value Co-creation - Ahmad, Farooq; Mustafa, Khurram; Hamid, Syed Ali Raza; Khawaja, Kausar Fiaz; Zada, Shagufta; Jamil, Saqib; Qaisar, Muhammad Nawaz; Vega-Muñoz, Alejandro; Contreras-Barraza, Nicolás; Anwer, Naveed (Frontiers in Psychology, 2022)
With the increasing growth of online shopping, businesses are intertwining to establish new shopping antecedents. Customer experience has steadily become the most important source of retailers' long-term competitive advantage via difference. To preserve long-term consumer loyalty and achieve sustainability, retailers must continually improve the customer experience. The study aims to determine what elements impact consumer satisfaction and loyalty. The study presents a complete model framework for online retailing in a digital environment called the Online Customer Experience-Engagement Context model. In a regulated method, the research also investigates the notion of value co-creation. Data was gathered from 189 people who purchased products online. For additional analysis, testing the hypothesis, and model construction, SPSS 26 and Smart-PLS were used. The data was then evaluated further using descriptive statistics, path analysis, measurement, and structural model. The findings show that the antecedent's shopping environment, shopping procedure, staff service experience, and product experience substantially influenced consumer engagement. With a bare minimum level of value co-creation, the evolving notion of value co-creation altered the overall link between the antecedent of Online Customer Experience and customer engagement. As a result, including consumers in co-creating, a delightful Online Customer Experience from time to time may be a valuable strategy for online retailers to increase customer engagement and loyalty. To create an overarching outcome, information integration theory (IIT), multi-attribute utility theory (MAUT), and the attitude-behavior-context theory (ABC) theories are converged in the study.